2020
DOI: 10.3389/fmicb.2020.01371
|View full text |Cite
|
Sign up to set email alerts
|

Application of Next-Generation Sequencing to Reveal How Evolutionary Dynamics of Viral Population Shape Dengue Epidemiology

Abstract: Dengue viral (DENV) infection results in a wide spectrum of clinical manifestations from asymptomatic, mild fever to severe hemorrhage diseases upon infection. Severe dengue is the leading cause of pediatric deaths and/or hospitalizations, which are a major public health burden in dengue-endemic or hyperendemic countries. Like other RNA viruses, DENV continues to evolve. Adaptive mutations are obscured by the major consensus sequence (so-called wild-type sequences) and can only be identified once they become t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 86 publications
1
15
0
1
Order By: Relevance
“…No such sequence variations were observed in the domain II, 3 UTR of DENV3 and DENV1 sequences identified in the current study and the human-and mosquito-derived sequences in the domain II, 3 UTR were identical in their respective serotypes (Table 1). However, adaptive mutations within the minor DENV populations within each host are known to be obscured by wild-type sequences and only revealed once they become dominant in the virus population and deep sequencing experiments are warranted to inference further in this regard [60]. The present study confirmed the reportedly high conservation of the RCS2 and CS2 regions in domain II, 3 UTR as shown by de Castro et al [55] in is his study of human-and mosquito-derived samples [55].…”
Section: Discussionsupporting
confidence: 83%
“…No such sequence variations were observed in the domain II, 3 UTR of DENV3 and DENV1 sequences identified in the current study and the human-and mosquito-derived sequences in the domain II, 3 UTR were identical in their respective serotypes (Table 1). However, adaptive mutations within the minor DENV populations within each host are known to be obscured by wild-type sequences and only revealed once they become dominant in the virus population and deep sequencing experiments are warranted to inference further in this regard [60]. The present study confirmed the reportedly high conservation of the RCS2 and CS2 regions in domain II, 3 UTR as shown by de Castro et al [55] in is his study of human-and mosquito-derived samples [55].…”
Section: Discussionsupporting
confidence: 83%
“…Several investigations showed evidence of a strong association between the genetic composition of intrahost viral populations and viral fitness and pathogenicity [ 9 , 10 , 11 , 12 ], especially lately that high-coverage and accurate whole-genome sequencing provided proof that fitness and adaptability variations occur without changes in the viral consensus sequence [ 19 , 20 , 50 ]. However, as recently reviewed by Ko et al, few studies tracked intrahost DENV diversity under epidemiological settings [ 19 , 20 , 50 , 51 ]. All of them combined viral genome PCR amplification + deep sequencing experimental strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial evidence indicates that variation in the DENV genome of serotypes and strains can have epidemiological significance by altering the extrinsic incubation period (EIP) [ 5 7 ], defined as the time it takes for the pathogen to be transmitted by the vector [ 8 ], and therefore has a powerful effect on the scale and speed of epidemics. DENV-2 strains from the American and Southeast Asian genotypes differ in their EIP lengths, with the Southeast Asian genotypes having shorter EIPs.…”
Section: Introductionmentioning
confidence: 99%